A constituição de surdos em alunos no contexto escolar: conflitos, contradições e exclusões - Abreu, Márcia Cristina Barreto Fernandes de (2016)
The objectives the thesis are discuss and analyze the meanings and senses of school practices, which constitute the sayings of deaf students. They were used as theoretical and methodological supports: Discourse Analysis (Pêcheux, 2012), concepts of psychoanalysis Freudo Lacanian (Freud, 1921; Lacan, 2008; Teixeira, 2005 and others) and studies on sign language (Skliar, 1998; Sacks, 2000; Quadros and Karnopp, 2004). For the construction of the research corpus were two interviews with six deaf students, aged one twenty-six years, in the final years of elementary school (8 and 9 years) in a public school in the city of Uberlândia - MG . Interviews were conducted in Libras (Brazilian Sign Language), interpreted simultaneously in Portuguese (oral) and recorded audio and video. The information processed by the survey suggests that the constitution of the deaf in student results, first, the deaf\'s relationship with his deafness. Second, the need for access to a language so that communication can be developed and expanded. Research has shown that LIBRAS appears as a language that favors the development and communication of the deaf. Third research shows that school, to prioritize the Portuguese language (written and oral), to the detriment of a bilingual approach (LIBRAS- Portuguese), has lead the deaf student to live a situation of conflict, contradictions and exclusions within the school context, and to develop a kind of school interpreter dependence.